The Family Coping Towards an Effectiveness of Family Health Management Among Hypertension Patients in Jombang - Fitria, Ony Nur; Urifah, Siti; Nasrudin; Rajin, Mukhamad (Al-Hijrah Indonesia, 2024)
Background: Hypertension is one silent killer and commonly occurred among elder people. Family health management is main factor to support elder people who have hypertension especially to prevent complications of hypertension. Objective: to analyze the relationship between family coping support and the effectiveness of family health management in family members with hypertension in Kepanjen Village, Jombang. Methods: This research method was correlation analytic with a cross-sectional approach, 158 families are the population in this study, 61 respondents were selected by using simple random sampling. All data collected by using questionnaires of family coping support and family health management. The data was analyzed by using Spearman rho test with significant value was p = 0.000. Results: The results of this study prove that family coping support is categorized as good with a score of 49.2% and the effectiveness of family health management is categorized as good with a score of 49.2%. The correlation coefficient value is 0.844 with a significance value of p = 0.000, which means the hypothesis is accepted, there is a relationship between family coping support and the effectiveness of family health management in family members with hypertension in Kepanjen Village, Jombang. Conclusion: Good family coping support is main factor in achieving effective family health management, because it can be controlled and can prevent the complications among hypertension patients.